New Record of Bar-Necked Keelback, Fowlea schnurrenbergeri (Kramer, 1977) (Squamata: Colubridae) in Bangladesh - Mahamud, Iftiker; Asif, Adnan Azad; Shome, Ashikur Rahman; Rahman, Md Mahfuzur (Bangladesh Journal of Zoology, 2022)
Abstract not available Bangladesh J. Zool. 50 (2): 273-276, 2022